An Analysis Of Post-Traumatic Stress Disorder (PTSD) OF Main Character In “A Private War” Film - Ayu Kartika Septiana; Mawa I Wayan; Prastikayanti Komang Sri (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2022)
The purpose of this study is to analyze the gestures and speech shown by the main character of the film who have mental disorders, especially post-traumatic stress disorder. In the analysis, the researcher took "A Private War" film as a subject of this research with a case study of mental disorders, namely post-traumatic stress disorder (PTSD). The researcher used qualitative method in descriptive form it tells the story of the main character (Marie Colvin), a war journalist who suffers from mental disorders after experiencing a traumatic event while covering a war. The results of this research show the description of 10 gestures and 5 speeches main character with post-traumatic stress disorder they are experiencing or witnessing a life-threatening event that causes intense fear, helplessness, or horror, Act or feel as if the event is happening again, flashbacks or a sense of reliving it, sleep disturbances and alcoholism, nervous and easily worried, having experienced terrible events, something is disturbed, and this has caused the emergence of memories associated with an event, and It is hard to believe in strangers they meet. Researcher hopes this research will be useful for readers to understand mental disorders, especially post-traumatic stress disorder.